Critical issue on the extinction and inattention subtest of NIHSS scale: an analysis on post-acute stroke patients attending inpatient rehabilitation - Benedetta Basagni; Bahia Hakiki; Silvia Campagnini; Emilia Salvadori; Antonello Grippo; Anita Paperini; Chiara Castagnoli; Ines Hochleitner; Angela Maria Politi; Paola Gemignani; Irene Eleonora Mosca; Azzurra Franceschini; et al. (BMC Neurology, 2021)
Abstract Objectives This study aims to evaluate the diagnostic performance of NIHSS extinction and inattention item, compared to the results of the Oxford Cognitive Screen (OCS) heart subtest. Additionally, the possible role of the NIHSS visual field subtest on the NIHSS extinction and inattention subtest performance is explored and discussed. Methods We analysed scores on NIHSS extinction and inattention subtest, NIHSS visual field subtest, and OCS heart subtest on a sample of 118 post-stroke patients. Results Compared to OCS heart subtest, the results on NIHSS extinction and inattention subtest showed an accuracy of 72.9% and a moderate agreement level (Cohen’s kappa = 0.404). Furthermore, a decrease in NIHSS accuracy detecting neglect (61.1%) was observed in patients with pathological scores in NIHSS visual field item. Conclusions Extreme caution is recommended for the diagnostic performance of extinction and inattention item of NIHSS. Signs of neglect may not be detected by NIHSS, and may be confused with visual field impairment. Trial registration This study refers to an observational study protocol submitted to ClinicalTrials.gov with identifier: NCT03968627 . The name of the registry is “Development of a National Protocol for Stroke Rehabilitation in a Multicenter Italian Institution” and the date of the registration is the 30th May 2019.